Influence of moisture content on the strength of weathered sandstone - Mohamad, Edy Tonnizam; Komoo, Ibrahim; Kassim, Khairul Anuar; Gofar, Nurly (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2008)
Variation of moisture content of weathered rock is an important issue in the tropical climate as extreme temperature and heavy downpour accelerate the changes in rock properties. This paper presents the results of excavatability study on sandstones of various weathering stages focusing on the effect of moisture content on their strength. Penetration tests were carried out on 127 samples collected from four sites in Bukit Indah, Kempas, Desa Tebrau and Mersing of Johor State. The resistance at 10 mm penetration of Universal Testing Machine is indicative of penetration index of the rock materials, to allow the prediction of rock strength. There is a significant relationship among weathering grades, moisture absorption and strength of rock. This is due to the microstructure changes in the rock in relation to weathering process that controls their physical and mechanical properties. The study revealed that fabric characteristics and pore spaces are very important for assessing the behaviour of weathered rock